2005
DOI: 10.1093/ndt/gfi163
|View full text |Cite
|
Sign up to set email alerts
|

The unrecognized prevalence of chronic kidney disease in diabetes

Abstract: Undiagnosed CKD is common in diabetes. Current screening strategies, based on creatinine or albuminuria, fail to identify a considerable number of subjects with CKD. Incorporating eGFR into screening for CKD would identify individuals earlier in the natural history of the disease and enable early effective treatment to delay progression of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
71
6
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 16 publications
14
71
6
6
Order By: Relevance
“…A similar prevalence was obtained in KEEP Mexico [21] as well as in Japan [22]. In two other investigations involving adult patients with diabetes, pathological albuminuria was found in 20.4% to 48.6% and reduced eGFR in 27.5% and 38% [23,24]. However, several studies showed that 10-25% patients with DM1 and DM2 had a non-albuminuric pathway to renal impairment [6,25,26].…”
Section: Discussionsupporting
confidence: 75%
“…A similar prevalence was obtained in KEEP Mexico [21] as well as in Japan [22]. In two other investigations involving adult patients with diabetes, pathological albuminuria was found in 20.4% to 48.6% and reduced eGFR in 27.5% and 38% [23,24]. However, several studies showed that 10-25% patients with DM1 and DM2 had a non-albuminuric pathway to renal impairment [6,25,26].…”
Section: Discussionsupporting
confidence: 75%
“…33 In two other studies examining adult patients with diabetes, albuminuria was found in 20.4-48.6% and reduced eGFR in 27.5 and 38%. 34,35 Moreover, Barrios et al 36 found GFR less than 60 mL/min/1.73 m 2 in 24.6% of patients with hypertension and chronic ischemic heart disease. It should be underlined that all these studies where a high prevalence of CKD in persons at risk of CKD was found, including our study, showed that most or even all patients with detected markers for CKD denied any knowledge of their kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increased risk of CKD in patients with diabetes, evidence suggests that the rate of progression of CKD is usually faster among diabetic than non-diabetic individuals 1) . Despite these observations, CKD -particularly in diabetic patients -is often underdiagnosed and undertreated 8,[14][15][16][17][18] . For example, in the interim analysis of the Atorvastatin Lipid Lowering Assessment Survey in Patients with Hypercholesterolemia (ALWAYS) trial 18) , a post-marketing surveillance study of atorvastatin in Japan, the primary physician diagnosed 8% of the cases as having CKD.…”
Section: Lipid Targets and Treatment Options For Patients With Ckd Anmentioning
confidence: 99%